The subprime financial crisis: a framework for future systemic financial stability - Bhimjee, Diptes Chandrakante Prabhudas (2016)
The present Document critically analyses the main causes leading to the Subprime Financial Crisis, not only by examining the performance of its underlying real estate and credit asset bubbles, but also by appraising the innovative financial instruments associated with the latter’s expansion, and by characterising the transmission channels associated with the deflating of the said bubbles. Furthermore, a review of the ensuing monetary regulatory response is also conducted, by introducing a classification of the event under study, exposing a potential drawback within the framework of the said response, and also by pinpointing some idiosyncrasies pertaining to the financial crisis under scrutiny. In addition, a more embracing future macroeconomic setting is prescribed, based on a more attentive microeconomic foundation favouring the regulation of financial risk, a framework which is rooted on an existing tutelary precedent, as exemplified by the current regulatory experience pertaining to the ‘carbon markets’. Finally, where a more appropriate regulatory mechanism in defence of a more tightened monetary stance is concerned, the enactment of a novel market-based regulatory protocol is carefully expounded and detailed, so that the costs associated with excessive and unregulated risk-taking that might lead to the occurrence of future financial crisis may be duly internalised, and, therefore, curtailed.